UX/UI Design 2022 : a comprehensive UI & UX guide to master web design and mobile app sketches for beginners and pros - Jones, Carl ([United States of America] : [Carl Jones], 2022)
UI/UX designing has become one of the most sought-after skills in the world today. This is because it offers a lot of opportunities in the design and tech space. Without any form of experience, there are core practical steps that you can take as a designer to get your journey started. Of course, all that you need to take this bold step has been strategically drafted in this book to get your experience hands-on. From mobile experiences to web experience, the intrinsic steps you need to take as a UI/UX designer have been highlighted in this book. First, it takes into the world of designing as a whole and what UI/UX seeks to achieve, as regards the experiences of users. You will understand the core aspect of the craft, from start to finish. additionally, the author has adopted a practical approaching to begin your design journey. You will be put through the paces into making your first design. The software and tools you need will unravel as you seek to get your journey started in the most impeccable way.
Chapter 1. What is Design -- Chapter 2. UI Design: Visual Design Principles -- Chapter 3. Typography of UI Design -- Chapter 4. Designs System and FIGMA -- Chapter 5. Psychology of colors in UI Designs.
Design 2022 :, UX
Keywords: COMPUTER SOFTWARE